The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s00405-022-07816-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of vestibular function and hearing in children with congenital cytomegalovirus infection: a prospective cohort study

Abstract: Purpose Congenital cytomegalovirus infection (cCMV) is the most frequent nonhereditary cause for sensorineural hearing loss (SNHL) in children. Data on vestibular function in children with cCMV are, however, scarce, although some evidence for cCMV-associated vestibular dysfunction exists. In this prospective cohort study, we evaluated long-term vestibular function and hearing outcomes in a cohort of children with cCMV. Methods Participants were 6–7-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…This might be largely due to the fact that our proportion of symptomatic patients (45%) was considerably smaller compared with most previous studies in which the majority of patients were symptomatic (Pappas 1983;Karltorp et al 2014;Bernard et al 2015;Chebib et al 2022a). Indeed, a vestibular dysfunction rate (19%) similar to our rate was reported in a recent study of Kokkola et al (2023) in a group of 36 cCMV-patients identified through population-based cCMV screening.…”
Section: Characteristics Of Ccmv-induced Vestibular Losssupporting
confidence: 90%
See 3 more Smart Citations
“…This might be largely due to the fact that our proportion of symptomatic patients (45%) was considerably smaller compared with most previous studies in which the majority of patients were symptomatic (Pappas 1983;Karltorp et al 2014;Bernard et al 2015;Chebib et al 2022a). Indeed, a vestibular dysfunction rate (19%) similar to our rate was reported in a recent study of Kokkola et al (2023) in a group of 36 cCMV-patients identified through population-based cCMV screening.…”
Section: Characteristics Of Ccmv-induced Vestibular Losssupporting
confidence: 90%
“…In fact, as vestibular loss occurred in only 5% of second trimester seroconversions and none of the third trimester seroconversions, these patients and their parents can be fairly reassured. Apart from these 2 predictors that are, to a greater or lesser extent, already described in literature (Zagólski 2008; Karltorp et al 2014; Bernard et al 2015; Chatzakis et al 2020; Dhondt et al 2020; Chebib et al 2022a, 2022b; Kokkola et al 2023), the predictive value of periventricular cysts on MRI also looks promising. When available, these data could add to the accuracy to predict vestibular outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term follow-up of children with cCMV is essential to identify those with late-onset hearing loss [44]. Moreover, as a recent study reported that vestibular dysfunction was more common than SNHL at 6 years of age, the inclusion of vestibular tests in the follow-up protocol for cCMV could also be considered in children with normal hearing [45].…”
Section: Discussionmentioning
confidence: 99%